Environmental Law and Policy in BRICS Countries: Legal Analyses of Sustainable Development Goals and Enforcement Strategies’ ’Human Rights in BRICS: A Comparative Approach to International Standards and Domestic Legal Systems - Rahmawati, Diah Ayu; Haryono, Haryono; Utari, Woro; Prayogi, Yoga Adi; Hartantien, Sinarianda Kurnia (West Science Social and Humanities Studies, 2024)
This paper examines the legal frameworks and enforcement strategies related to environmental governance and human rights in BRICS countries-Brazil, Russia, India, China, and South Africa. Through normative analysis, the study explores the alignment of national laws with Sustainable Development Goals (SDGs) and international human rights standards. The findings reveal significant variations in legislative approaches and enforcement mechanisms across BRICS nations, influenced by socio-economic priorities and institutional capacities. The analysis highlights the challenges of balancing economic growth with sustainability and social equity while identifying best practices and opportunities for regional collaboration. This study contributes to the discourse on sustainable development by emphasizing the need for integrated legal approaches to environmental governance and human rights protection in BRICS countries.